2016
DOI: 10.1097/prs.0000000000002005
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Safety and Efficacy of Gluteal Augmentation: A Systematic Review of Outcomes and Complications

Abstract: Although gluteal augmentation was once reported to have complication rates as high as 38.1 percent, a systematic review of the two most popular techniques demonstrated substantially lower overall complication rates. The overall complication rate with autologous fat grafting (9.9 percent) is lower than that with silicone buttock implants (21.6 percent). A standardized method of measuring patient satisfaction is necessary to fully understand outcomes of these increasingly popular procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(44 citation statements)
references
References 18 publications
1
43
0
Order By: Relevance
“… 31 In 2016 Sinno et al published a comparison of satisfaction and complications between silicone implants and lipoinjection. 32 They identified a total of 3567 gluteal augmentation patients in the studies that fulfilled their search criteria. They concluded that the rate of complications was lower with lipoinjection, although there were deaths in their review of gluteal augmentation with fat but not with silicone buttock implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 In 2016 Sinno et al published a comparison of satisfaction and complications between silicone implants and lipoinjection. 32 They identified a total of 3567 gluteal augmentation patients in the studies that fulfilled their search criteria. They concluded that the rate of complications was lower with lipoinjection, although there were deaths in their review of gluteal augmentation with fat but not with silicone buttock implants.…”
Section: Discussionmentioning
confidence: 99%
“…Also in 2016, Conde-Green et al published a systemic review of the literature and meta-analysis, and found 19 articles made up of 17 case studies and two retrospective studies for a total of 4105 patients (these include the cases in the Sinno review). 32 They found that 46.7% of the articles recommended fat injections into both the subcutaneous and intramuscular planes, 26.7% into only the intramuscular planes, and 26.7% into the subcutaneous or subfascial planes. 25 Cárdenas-Camarena first reported on nonfatal PFE in 1999 and Astarita first described a fatal PFE in a 2015 case report.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the most commonly reported complications in 2375 patients receiving silicone implants were wound dehiscence (9.6%), seroma (4.6%), infection (1.9%), and transient sciatic paresthesias (1.0%), with an overall complication rate of 21.6%. 19 No distant silicone complications were reported using implants.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the relative paucity of data, the complication profile of gluteal augmentation has been reviewed. Sinno et al 1 conducted an extensive database analysis and found the overall complication rate of gluteal fat grafting to be 9.9%, whereas the rate of sciatic pain was reported at 1.7%. In their world literature review, Oranges et al 2 reported a complication rate of 10.5% and 1 incident of bilateral sciatic nerve axonotmesis (0.04%) following autologous fat grafting.…”
Section: Discussionmentioning
confidence: 99%